Matrix delivery transdermal 17beta-estradiol for the prevention of bone loss in postmenopausal women. The International Study Group. - Cooper, C; Stakkestad, J; Radowicki, S; Hardy, P; Pilate, C; Dain, M; Delmas, P (1999)
A total of 277 early postmenopausal women were enrolled in this placebo-controlled 2-year study to examine the efficacy of a matrix transdermal 17beta-estradiol system, at three different dosages (25, 50 and 75 mg/day) combined with sequential oral dydrogesterone 20 mg/day, in preventing bone loss. At 2 years, the difference from placebo in percentage change from baseline of L1-4 lumbar spine bone mineral density (BMD) (assessed by dual-energy X-ray absorptiometry) was 4.7% +/- 0.7% with estradiol 25 mg/day, 7.3% +/- 0.7% with estradiol 50 mg/day and 8.7% +/- 0.7% with estradiol 75 mg/day (all values mean +/- SEM). There were also significant increases in femoral neck, trochanter and total hip BMD with all doses of estradiol compared with placebo. Additionally, most patients had a significant gain (increase greater than 2.08%) in lumbar spine bone mass compared with placebo. Patients who received estradiol also experienced clinically significant and dose-related decreases in total serum osteocalcin, serum bone alkaline phosphatase and urinary C-telopeptide, with all three markers of bone turnover returning to premenopausal levels. Estradiol was well tolerated during the 2-year treatment period. Transdermal estradiol is effective and well tolerated at dosages between 25-75 mg/day in the prevention of bone loss in postmenopausal women; 25 mg/day offers an effective option for those women who cannot tolerate higher doses.